Impact of aging and body mass index on upper extremity motor unit number index and size - Lauren I. Gulley Cox; Nicholas Dias; Chuan Zhang; Yingchun Zhang; Stacey L. Gorniak (Experimental Biology and Medicine)
The focus of this study was to evaluate motor unit number and size across the upper extremity in older adults (aged 60+ years) versus young healthy adults (aged 20–30 years). We hypothesized that older adults would have: fewer motor units and increased motor unit size as compared to young healthy adults (H1), that motor unit size would differ across the upper extremity muscles as compared to young healthy adults (H2), and higher body mass index (BMI) would be associated with lower motor unit numbers (H3). Compound muscle action potential (CMAP), motor unit number index (MUNIX), and motor unit size index (MUSIX) were evaluated in five muscles of the upper extremity. Group differences in CMAP due to aging were accounted for by increased body mass index (BMI); group differences in MUSIX were not impacted by BMI. No difference in MUNIX was found; however, an influence of BMI was found across groups. While this data provides supporting evidence of age-related motor unit changes, body composition changes with age may confound these conclusions when surface electromyography is utilized as the measurement modality. Adiposity estimation should be considered in future EMG studies, particularly in populations with higher BMI values.